Die erfolgreiche Bindung des Sparers an die Bank - Sievers, Sönke; Schlüter, Tobias; Hartmann-Wendels, Thomas (Börsen-Zeitung)

Wie Banken Kostenvorteile weitergeben - Sievers, Sönke; Hartmann-Wendels, Thomas; Busch, Ramona; Schlüter, Tobias (Börsen-Zeitung)

Identifikation und Wiederherstellung von kryptographischen Schlüsseln mit FPGAs - Riebler, Heinrich
Keywords: coldboot

HSkip+: A Self-Stabilizing Overlay Network for Nodes with Heterogeneous Bandwidths - Feldotto, Matthias

How many attackers can selfish defenders catch? - Mavronicolas, Marios; Monien, Burkhard; Papadopoulou Lesta, Vicky (Discrete Applied Mathematics)
In a distributed system with attacks and defenses, both attackers and defenders are self-interested entities. We assume a reward-sharing scheme among interdependent defenders; each defender wishes to (locally) maximize her own total fair share to the attackers extinguished due to her involvement (and possibly due to those of others). What is the maximum amount of protection achievable by a number of such defenders against a number of attackers while the system is in a Nash equilibrium? As a measure of system protection, we adopt the Defense-Ratio (Mavronicolas et al., 2008)[20], which provides the expected (inverse) proportion of attackers caught by the defenders. In a Defense-Optimal Nash equilibrium, the Defense-Ratio matches a simple lower bound.We discover that the existence of Defense-Optimal Nash equilibria depends in a subtle way on how the number of defenders compares to two natural graph-theoretic thresholds we identify. In this vein, we obtain, through a combinatorial analysis of Nash equilibria, a collection of trade-off results:• When the number of defenders is either sufficiently small or sufficiently large, Defense-Optimal Nash equilibria may exist. The corresponding decision problem is computationally tractable for a large number of defenders; the problem becomes NPNP-complete for a small number of defenders and the intractability is inherited from a previously unconsidered combinatorial problem in Fractional Graph Theory.• Perhaps paradoxically, there is a middle range of values for the number of defenders where Defense-Optimal Nash equilibria do not exist.

Hierarchies in Local Distributed Decision - Meyer auf der Heide, Friedhelm; Swirkot, Kamil
We study the complexity theory for the local distributed setting introduced by Korman, Peleg and Fraigniaud. They have defined three complexity classes LD (Local Decision), NLD (Nondeterministic Local Decision) and NLD^#n. The class LD consists of all languages which can be decided with a constant number of communication rounds. The class NLD consists of all languages which can be verified by a nondeterministic algorithm with a constant number of communication rounds. In order to define the nondeterministic classes, they have transferred the notation of nondeterminism into the distributed setting by the use of certificates and verifiers. The class NLD^#n consists of all languages which can be verified by a nondeterministic algorithm where each node has access to an oracle for the number of nodes. They have shown the hierarchy LD subset NLD subset NLD^#n. Our main contributions are strict hierarchies within the classes defined by Korman, Peleg and Fraigniaud. We define additional complexity classes: the class LD(t) consists of all languages which can be decided with at most t communication rounds. The class NLD-O(f) consists of all languages which can be verified by a local verifier such that the size of the certificates that are needed to verify the language are bounded by a function from O(f). Our main results are refined strict hierarchies within these nondeterministic classes.

Haptics - Hadoop performance testing in concurrent job scenarios - Niklas Vinkemeier, Tim

Greedy Network Creation With Heavy And Light Edges - Mäcker, Alexander

Fuzzy Service Matching in On-The-Fly Computing - Christin Platenius, Marie (Proceedings of the Doctoral Symposium of the 9th joint meeting of the European Software Engineering Conference (ESEC) and the ACM SIGSOFT Symposium on the Foundations of Software Engineering (FSE))
In the future vision of software engineering, services from world-wide markets are composed automated in order to build custom-made systems.Supporting such scenarios requires an adequate service matching approach.Many existing approaches do not fulfill two key requirements of emerging concepts like On-The-Fly-Computing, namely (1) comprehensiveness, i.e., the consideration of different service aspects that cover not only functional properties, but also non-functional properties and (2) fuzzy matching, i.e., the ability to deliver gradual results in order to cope with a certain extent of uncertainty, incompleteness, and tolerance ranges.In this paper, I present a fuzzy matching process that distinguishes between different fuzziness sources and leverages fuzziness in different matching steps which consider different service aspects, e.g., behavior and quality properties.

Executing Reconfigurations in Hierarchical Component Architectures - Heinzemann, Christian; Becker, Steffen (Proceedings of the 16th International ACM SigSoft Symposium on Component-Based Software Engineering (CBSE))
Mechatronic systems reconfigure the structure of their software architecture, e.g., to avoid hazardous situations or to optimize operational conditions like minimizing their energy consumption. As software architectures are typically build on components, reconfiguration actions need to respect the component structure. This structure should be hierarchical to enable encapsulated components. While many reconfiguration approaches for embedded real-time systems allow the use of hierarchically embedded components, i.e., horizontal composition, none of them offers a modeling and verification solution to take hierarchical composition, i.e., encapsulation, into account. In this paper, we present an extension to our existing modeling language, MechatronicUML, to enable safe hierarchical reconfigurations. The two main extensions are (a) an adapted variant of the two-phase commit protocol to initiate reconfigurations which maintain component encapsulation and (b) a timed model checking verification approach for instances of our model. We illustrate our approach on a case study in the area of smart railway systems by showing two different use cases of our approach and the verification of their safety properties.

Entwurf kooperativer Verhaltensweisen heterogener Roboter - Buse, Dominik

Entwurf eines datenschutzgerechten Reputationssystems - Lutters, Sascha

Entwicklung und Analyse einer verteilten Speicherverwaltung für dynamische heterogene Speichersysteme - Hilleckes, Hendrik

Entwicklung eines Hybriden Planers zur verhaltensorientierten Selbstoptimierung - Borkowski, Richard

Emulating Wavelength Division Multiplexing using Openflow - Satya, Suhas

Effizienzsteigerung durch gewichtete Produktbewertungen - Reineke, Max

Dynamic One-to-One Matching: Theory and a Job Market Application - Stroh-Maraun, Nadja

Dispersion of Multi-Robot Teams - Heindorf, Stefan

Direct Chosen-Ciphertext Secure Attribute-Based Key Encapsulations without Random Oracles - Blömer, Johannes; Liske, Gennadij
We present a new technique to realize attribute-based encryption (ABE) schemes secure in the standard model against chosen-ciphertext attacks (CCA-secure). Our approach is to extend certain concrete chosen-plaintext secure (CPA-secure) ABE schemes to achieve more efficient constructions than the known generic constructions of CCA-secure ABE schemes. We restrict ourselves to the construction of attribute-based key encapsulation mechanisms (KEMs) and present two concrete CCA-secure schemes: a key-policy attribute-based KEM that is based on Goyal's key-policy ABE and a ciphertext-policy attribute-based KEM that is based on Waters' ciphertext-policy ABE. To achieve our goals, we use an appropriate hash function and need to extend the public parameters and the ciphertexts of the underlying CPA-secure encryption schemes only by a single group element. Moreover, we use the same hardness assumptions as the underlying CPA-secure encryption schemes.

Der Einfluss adaptierter Erwartungen in dynamischen Cournot Oligopolen - Kornhoff, Tobias